SARS-CoV-2 virus lacking the envelope and membrane open-reading frames as a vaccine platform - Makoto Kuroda; Peter J. Halfmann; Ryuta Uraki; Seiya Yamayoshi; Taksoo Kim; Tammy A. Armbrust; Sam Spyra; Randall Dahn; Lavanya Babujee; Yoshihiro Kawaoka (Nature Communications)
Abstract To address the need for broadly protective SARS-CoV-2 vaccines, we developed an attenuated a SARS-CoV-2 vaccine virus that lacks the open reading frames of two viral structural proteins: the envelope (E) and membrane (M) proteins. This vaccine virus (ΔEM) replicates in a cell line stably expressing E and M but not in wild-type cells. Vaccination with ΔEM elicits a CD8 T-cell response against the viral spike and nucleocapsid proteins. Two vaccinations with ΔEM provide better protection of the lower respiratory tissues than a single dose against the Delta and Omicron XBB variants in hamsters. Moreover, ΔEM is effective as a booster in hamsters previously vaccinated with an mRNA-based vaccine, providing higher levels of protection in both respiratory tissues compared to the mRNA vaccine booster. Collectively, our data demonstrate the feasibility of a SARS-CoV-2 ΔEM vaccine candidate virus as a vaccine platform.